2011
DOI: 10.3892/ijmm.2011.656
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin promotes the proliferation of gastric cancer cells via the Toll-like receptor 5

Abstract: Abstract.Signaling of the Toll-like receptor (TLR) is closely associated with tumor development and progression processes including cell proliferation, angiogenesis, metastasis, and immunosuppression. In this study, we examined the expression of TLR5 in gastric cancer cells and its function in cell proliferation. RT-PcR revealed that the TLR5 gene was expressed in all gastric cancer cell lines examined, SNU638, SNU601, SNU216, and AGS. The TLR5 agonist, flagellin, induced IL-8 production and NF-κB activation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Previously, intense links have emerged between inflammation and the initiation and progression of several cancer types, including stomach, breast, ovary and liver (19). Chronic inflammation elicited by certain bacteria, for instance Helicobacter pylori , has been found to promote carcinogenesis (20). Activation of TLRs may favor a contribution for cancer progression and development, however, activation of various TLRs may exhibit contradictory results (21).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, intense links have emerged between inflammation and the initiation and progression of several cancer types, including stomach, breast, ovary and liver (19). Chronic inflammation elicited by certain bacteria, for instance Helicobacter pylori , has been found to promote carcinogenesis (20). Activation of TLRs may favor a contribution for cancer progression and development, however, activation of various TLRs may exhibit contradictory results (21).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Chochi et al (104) not only showed that H. pylori augmented the growth of GC via the LPS-TLR4 pathway but also found that this bacterium attenuated the antitumor activity and IFN-γ-mediated cellular immunity of human mononuclear cells. In addition, Song et al (131) have suggested that flagellin-activated TLR5 enhances the proliferation of GC cells through an ERK-dependent pathway. Furthermore, Tye et al (132) have proposed a novel role for TLR2 in promoting gastric tumorigenesis independent of inflammation, whereby up-regulation of TLR2 within epithelial tumor cells, rather than infiltrating inflammatory cells, by the uncontrolled activation of the oncogenic transcription factor STAT3, promoted gastric tumor cell proliferation, and survival via up-regulation of anti-apoptotic genes [e.g., BCL2-related protein A1 ( BCL2A1 ), baculoviral IAP repeat containing 3 ( BIRC3 ), and B-cell CLL/lymphoma 3 ( BCL3 )].…”
Section: Toll-like Receptors and Helicobacter Pylori-related Gastric mentioning
confidence: 99%
“…For example, TLR5 is highly expressed in breast carcinoma and gastric carcinoma cells, and TLR5 signaling inhibits breast cancer growth, but promotes the proliferation of gastric cancer cells. [9,12,19] However, it is not all the TLRs expressed in cancer cells are functional to induce inflammatory response. In breast cancer cell MDA-MB-231 and MDA-MB-435, TLR5 is abnormally localized only in cytoplasm, so NF-κB signaling cannot be activated by TLR5 agonist in these cells.…”
Section: Resultsmentioning
confidence: 99%